If you must use embargoes, here’s how to do it right (Epidemiology, Biostatistics, and Public Health, 2022)
Embargoes - often used by scientific institutions such as medical societies and scientific journals to give access to reporters before material is published - can inspire heated arguments. Some journalists love them, while others say they - along with Ingelfinger Rule, which prohibits pre-publication publicity of results before they appear in a peer-reviewed journal - discourage original reporting [1]. Journals find them helpful in “choreographing” the dance of medical news [2], but some have eschewed them completely [3]. Despite all of this debate,…